On the theory of a pulse laser with microwave pumping - Семенець, В.В.; Копоть, М.А.; Грицунов, О.В.; Бондаренко, І.М.; Юнусов, Е.Е. (Radiotekhnika, 2019)
The construction of a laser with a microwave pumping based on the light-pumping cell that uses radiation of sulfur vapor exposed to electromagnetic waves of the microwave band is discussed. The advantages of this device are high efficiency of the optical pumping cell, simple structure, the possibility of cooling the pumping element, and easiness of modifying the emission spectrum of the optical pumping by changing the admixtures in the light-emitting cell. A mathematical tool for the simulation of the short-pulse operation of this laser is proposed basing on the solving a generalized wave equation. The microwave waveguide with the sulfur vapors is interpreted as a regular transmission line with essentially nonlinear dispersion characteristic and substantial dissipation. Possible techniques for the numerical solving the generalized wave equation are described. The continuous approximation of the regular dispersive line is used. In the Fourier approach, the electric field in the system is calculated as a series in the longitudinal wavenumber. As an alternative, the D’Alembert approach may be used, with evaluating the electric field as a series in the frequency. Three-layer explicit and implicit second-order approximation schemes for the solving generalized wave equation in the Fourier approach are constructed. The modeling of radio pulse propagation in the “cold” regular electrodynamic system was performed. Stability of the algorithm and qualitative agreement between the numerical and analytic results confirm the correctness of the base equations as well as their solutions based at the finite-difference schemes.